Chemical composition and nutritional effect of Physalis peruviana husk as hepato-renal protective agent - Souad E. El-Gengaihi; Manal A. Hamed; Emad El-Din Hassan; Emad El-Din Hassan; Hanan G. Zahran; Mona A. Mohammed (International Journal of Phytomedicine, 2012)
This work is designed to investigate the potential of Physalis peruviana as hepato-renal protective agent against fibrosis. Two compounds (15-desacetylphysabubenolide and Betuline) were isolated and their structures were elucidated. The biological evaluation was conducted on different rats groups; control, control treated with the methanolic husk extract, carbon tetrachloride (CCl4), CCl4 treated with husk extract and CCl4 treated with silymarin. The evaluation was done through measuring oxidative stress markers; malondialdehyde (MDA), superoxide dismutase (SOD) and nitric oxide (NO). Liver function indices; aspartate and alanine aminotransferases (AST & ALT), alkaline phosphatase (ALP), gamma glutamyl transferase (GGT), bilitubin and total hepatic protein were estimated. Kidney disorder biomarkers; creatinine, urea and serum protein were evaluated. The results revealed improvement of all the investigated parameters. Liver and kidney histopathologyical analysis confirmed our results. In conclusion, Physalis peruviana succeeded to protect liver and kidney against fibrosis. Further studies are needed for its pharmacological and clinical uses.